Obtaining ammonia fertilizer from coal Alai deposit of the Kyrgyz Republic (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In this paper, a technological scheme for the production of ammonium sulfate from coke oven gas has been investigated and developed. The mass concentrations of ammonia and ammonium ions (80 mg/dm3) were determined. It is shown that the total ammonia content in the above-ground water obtained from the coals of the Alai deposit of the Kyrgyz Republic is very small, with about 80-90% NH3 in the free state, and the rest in the form of ammonium salts: (NH4)2CO3, (NH4)2S, (NH4)2 SO4, NH4CL, NH4CNS, etc. From cooled, concentrated ammonia water by the reaction of 2NH4 ОН+H2 SO4 =(NH4)2 SO4+2Н2О, a fertilizer is formed - ammonium sulfate, i.e. the mineral fertilizer (NH4)2SO4 ammonium sulfate from coal from the Alai deposit of the Kyrgyz Republic.
Keywords: Pyrolysis, resin, pyrogenetic water, ammonia water, ammonium hydroxide, muffle furnace, gas collector, refrigerator, sump, steam, calcium hydroxide, ammonia, Nessler reagent, distillation column, buffer solution, mineral fertilizers, ammonium sulfate